Piecing it all together and forecasting who governs: The 2015 British general election - Fisher, S (Elsevier, 2015)
This paper discusses a new probabilistic forecasting method that was designed for the 2015 British general election. It proceeds in a series of steps from opinion poll averaging, forecasting national-level vote shares and uncertainty estimates, and subsequent simulation of hypothetical election results, through modelling of constituency polls and survey data to identify and adjust for patterns in the constituency-level variation in party performance, and finally to probabilistic forecasting of seat outcomes and of different combinations of parties commanding relevant governing majorities in parliament.